Continuous observations of the surface energy budget and meteorology over the Arctic sea ice during MOSAiC - Christopher J. Cox; Michael R. Gallagher; Matthew D. Shupe; P. Ola G. Persson; Amy Solomon; Christopher W. Fairall; Thomas Ayers; Byron Blomquist; Ian M. Brooks; Dave Costa; Andrey Grachev; Daniel Gottas; et al. (Scientific Data, 2023)
Abstract The Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) was a yearlong expedition supported by the icebreaker R/V Polarstern, following the Transpolar Drift from October 2019 to October 2020. The campaign documented an annual cycle of physical, biological, and chemical processes impacting the atmosphere-ice-ocean system. Of central importance were measurements of the thermodynamic and dynamic evolution of the sea ice. A multi-agency international team led by the University of Colorado/CIRES and NOAA-PSL observed meteorology and surface-atmosphere energy exchanges, including radiation; turbulent momentum flux; turbulent latent and sensible heat flux; and snow conductive flux. There were four stations on the ice, a 10 m micrometeorological tower paired with a 23/30 m mast and radiation station and three autonomous Atmospheric Surface Flux Stations. Collectively, the four stations acquired ~928 days of data. This manuscript documents the acquisition and post-processing of those measurements and provides a guide for researchers to access and use the data products.